Phytochemistry of the Carnivorous Sundew Genus Drosera (Droseraceae) – Future Perspectives and Ethnopharmacological Relevance. Issue 10 (16th October 2013) - Egan, Paul A.; van der Kooy, Frank
Abstract Species of the carnivorous genus Drosera L. have long been a source of valuable natural products. The various phytochemicals characteristic of these species, particularly 1, 4‐naphthoquinones and flavonoids, have contributed to the diverse utilization of sundews in traditional medicine systems worldwide. A growing number of studies have sought to investigate the comparative phytochemistry of Drosera species for improved sources of pharmaceutically important compounds. The outcomes of these studies are here collated, with emergent trends discussed in detail. Important factors which affect production of secondary metabolites in plants are critically examined, such as environmental influences and in vitro culture, and recommendations subsequently presented based on this. Explicitly, the current review aims to i) present an updated, comprehensive listing of the phytochemical constituents of the genus (including quantitative data where available), ii) summarize important factors which may influence the production of phytopharmaceuticals in plants, and iii) recommend guidelines for future research based on the above, including improved standardization and quality control. We have also included a section discussing future perspectives of research on Drosera spp. based on three different research lines i) the potential to produce much needed lead compounds for treatment of tuberculosis, ii) the potential role of anthocyanins in nitrogen transport, and iii) research into 'Natural Deep Eutectic' solvents produced by Drosera spp. in the droplets or 'dew' employed to capture insect prey.